DAMPAK MEDIA SOSIAL INSTAGRAM TERHADAP STYLE HIJAB: PERSPEKTIF MEDIA DALAM MODERNISASI (Program Studi Komunikasi dan Penyiaran Islam, 2025)
Instagram has become one of the most influential spaces shaping the hijab style preferences of FDIKOM UIN Jakarta students. The flow of modernization carried through visual content on this platform encourages the emergence of various hijab innovations that do not always align with Islamic guidelines. This study aims to examine how Instagram affects students’ choices, interpretations, and responses toward modern hijab trends. The research employed a constructivist paradigm using a phenomenological method, with data collected through observation, interviews, and documentation involving active Instagram users among the students. The findings show that some students adopt modern hijab styles for aesthetic and practical reasons, while others reject innovations they perceive as reducing the religious meaning of the hijab. The study concludes that Instagram does not merely disseminate trends but also shapes the students’ negotiation of Islamic identity within the dynamics of digital modernization